Analysis of the efficiency of theoretical knowledge and practical skills acquisition by intern doctors using the “Body Interact” virtual patient simulator in the conditions of today’s challenges - M. Yu. Kolesnyk; Ya. M. Mykhailovskyi (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2024)
The aim of the work is to evaluate the efficiency of theoretical knowledge and practical skills acquisition by intern doctors using the body interact virtual patient simulator in distance (offline) and traditional (online) form of education.